Analysis of Local Government Policies in Preventing and Reducing Stunting Rates in Sarappo Island, Mattiro Langi Village, Liukang Tupabbiring District, Pangkep Regency, Indonesia - Nurhalilah, Nurhalilah; Yunus, Rabina; Rusli, AM (Journal of Neonatal Surgery, 2025)
The problem of stunting is one of the significant health challenges in Indonesia, especially in remote areas such as Mattiro Langi Village, Liukang Tupabbiring District, Pangkep Regency. particularly on Sarappo Island. This study aims to analyze local government policies in preventing and reducing stunting rates and identify factors that influence the implementation of these policies. Using a descriptive qualitative approach, this study examines policies through three main stages, namely specific interventions, sensitive interventions, and education and socialization. The results of the study indicate that specific interventions involve providing Iron Supplement Tablets (TTD), promoting exclusive breastfeeding, and providing Complementary Foods (MP-ASI). Sensitive interventions include the implementation of the Dasyat (Healthy Kitchen) program which utilizes local food to improve the nutritional status of the community. Meanwhile, education and socialization are carried out through Posyandu to increase public awareness of the importance of nutrition and good parenting. Factors that influence policies include social, cultural, and economic constraints. Low public awareness, food myths, and economic limitations are the main obstacles. However, local policies such as budget allocation for food subsidies and health programs provide strategic solutions to overcome this problem. This study recommends improving culture-based education, optimizing social assistance programs, and building health and sanitation facilities to support a sustainable reduction in stunting rates in Mattiro Langi Village.